Evaluación de la ejecución presupuestaria en el Gobierno Autónomo Parroquial Rural Ángel Pedro Giler y su incidencia en el bienestar ciudadano - Almeida Rosado, Roberth Josué (2023)
The purpose of this investigation was to evaluate the budget execution in the Ángel Pedro Giler Rural Parochial Autonomous Government and its incidence on citizen well-being in the fiscal period 2021. To comply with the proposal, investigative methods such as the inductive-deductive were used. and synthetic analytical, in the same way, it was necessary to apply techniques for the collection of information such as the application of an interview with the secretary and treasurer of GAD and 399 surveys of citizens. As a first result, it was obtained that only 74% of the budget allocation was executed, thus contradicting the planning proposed in the POA and the PAC, which reflects deficient levels in the fulfillment of goals. The second result responds to the levels of satisfaction that citizens have based on budget planning and execution, evidencing that compliance with plans, projects and programs is unsatisfactory, due to poor management by parish leaders. As a last result, the proposal of the improvement plan is proposed to mitigate the shortcomings, where the problem lies in the fact that there is a low and insufficient level in the budget execution, for which strategies focused on the continuous improvement of the setting are proposed. budget planning and management, with the guarantee of maintaining efficient levels of citizen satisfaction.